2016
DOI: 10.2135/cropsci2015.06.0379
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Dhurrin QTL in Sorghum: Co‐localization of Dhurrin Biosynthesis and a Novel Stay‐green QTL

Abstract: Dhurrin [(S)‐p‐hydroxymandelonitrile‐β‐D‐glucopyranoside] is a cyanogenic glucoside produced by sorghum (Sorghum bicolor L. Moench) and is generally considered a natural defense compound capable of producing the toxin hydrogen cyanide (HCN) to deter animal herbivory. Recently, high levels of leaf dhurrin have been found in grain sorghum genotypes that also exhibit stay‐green during postanthesis water deficit. Post‐flowering drought tolerance (stay‐green) in sorghum is an economically important trait in sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Consequently, the most promising strategy to improve the performance of cereal crop plants under thermal stress appears to be source related, namely the introduction of functional stay-green traits that prevent precocious senescence. In sorghum, stay green has for instance been associated with the formation and presence of the cyanogenic glucoside dhurrin (Hayes et�al. 2015, Emendack et�al.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the most promising strategy to improve the performance of cereal crop plants under thermal stress appears to be source related, namely the introduction of functional stay-green traits that prevent precocious senescence. In sorghum, stay green has for instance been associated with the formation and presence of the cyanogenic glucoside dhurrin (Hayes et�al. 2015, Emendack et�al.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that sorghum dhurrin content in leaf tissue is controlled by genes involved the biosynthetic and catabolic pathways in different level of Nitrogen [ 54 ]. It was also reported that there is association between high leaf dhurrin content and expression of the stay-green trait [ 55 ]. An enzyme CYP79A1 [EC:1.14.13.41] that is grouped into a class of oxidoreductases and encoded by a putatively uncharacterised hypothetical protein gene ‘Sb01g001200’ was identified with a direct involvement in drought tolerance, as it was recently known to be aligned with dhurrin QTL that is associated with stay-green trait [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that there is association between high leaf dhurrin content and expression of the stay-green trait [ 55 ]. An enzyme CYP79A1 [EC:1.14.13.41] that is grouped into a class of oxidoreductases and encoded by a putatively uncharacterised hypothetical protein gene ‘Sb01g001200’ was identified with a direct involvement in drought tolerance, as it was recently known to be aligned with dhurrin QTL that is associated with stay-green trait [ 55 ]. A transcriptional regulation of this enzyme largely determines the synthesis of dhurrin, based on the developmental stage and growth condition of sorghum [ 53 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Categorization of materials into dhurrin levels, rather than dhurrin contents, was based on the fact that, while values for dhurrin contents varied with the different locations, high dhurrin-level lines always showed higher dhurrin content than low dhurrin-level lines in all locations used for evaluations by Burke et al (2013) and Hayes et al (2016). Sorghum materials used had known dhurrin levels (high or low), based on multiyear and multilocation assessments of dhurrin contents from leaves of plants at the late vegetative stage.…”
Section: Genotypes Used and Controlled Environment Practicesmentioning
confidence: 99%
“…Sorghum materials used had known dhurrin levels (high or low), based on multiyear and multilocation assessments of dhurrin contents from leaves of plants at the late vegetative stage. Categorization of materials into dhurrin levels, rather than dhurrin contents, was based on the fact that, while values for dhurrin contents varied with the different locations, high dhurrin-level lines always showed higher dhurrin content than low dhurrin-level lines in all locations used for evaluations by Burke et al (2013) and Hayes et al (2016). The germplasm used in this study came from the Cropping System Research Laboratory sorghum-breeding program at USDA-ARS, Lubbock, and included sorghum conversion lines, recombinant inbred lines (RILs, from a cross between staygreen BTx642 and senescence TX7000), a BTx623 EMS-induced F 2 mutant population, and breeding lines commonly used in sorghum breeding programs (Table 1).…”
Section: Genotypes Used and Controlled Environment Practicesmentioning
confidence: 99%